Comparative examination of the serological response to bluetongue virus in diseased ruminants by competitive and double recognition enzime-linked immunosorbent assays - GAVRILOVIĆ, A.; GAVRILOVIĆ, P.; RADOJIČIĆ, S.; KRNJAIĆ, D. (Journal of the Hellenic Veterinary Medical Society, 2018)
Bluetongue (BT) is a viral non-contagious disease of ruminants which is transmitted by insects of the genus Culicoides. In recent years, BT has been a serious threat to livestock and to the economies of European countries. In Serbia the disease appeared for the first time in 2001, and after a 12 year period of freedom, it broke out again in 2014. Considering the actuality of this infectious disease, especially the need for prompt and rapid diagnostics, the aim of this paper was to determine the possibility of detecting the serological response in sheep and cattle with manifested clinical signs of the disease using two different methods: double recognition enzyme-linked immunosorbent assay (sELISA) and competitive enzyme-linked immunosorbent assay (cELISA). A total of 105 blood serum samples of cattle and sheep, which had exhibited clinical signs of BT during 2014, were taken for examination from a serum bank. Out of 74 blood serum samples of sheep and 31 blood serum samples of cattle, 52 samples of sheep and 18 samples of cattle tested positive using sELISA, while 50 samples of sheep and 18 samples of cattle gave positive reactions with cELISA. The results confirm the high sensitivity of sELISA which detected 4% more seropositive sheep in comparison with cELISA. Using Cohen’s kappa statistical analysis, almost perfect agreement was determined between the results (k>0,81) obtained by cELISA and sELISA.